Towards objective endoscopic diagnosis of Barrett's associated early neoplasia using fibre-optic Raman Spectroscopy - Almond, Laurence Maximilian (Cranfield University, 2012)
This translational research evaluates a novel, custom-built Raman probe for potential application as an in vivo diagnostic tool in the oesophagus. Raman spectroscopy (RS) is a well established analytical technique which is capable of probing the biochemical changes associated with neoplastic progression in oesophageal tissue. RS relies on measurement of subtle inelastic scattering signals following monochromatic laser excitation. Clinical utilisation of RS within hollow organs requires accurate collection and transmission of signal through fibre-optic cables. This research aims to evaluate the ability of a custom built fibre-optic Raman probe, in conjunction with multivariate classification models, to differentiate between benign and neoplastic oesophageal pathologies ex vivo. The need for spectral stability and reproducibility are addressed, as are difficulties associated with multisystem reliability. In addition, the biochemical basis of spectral classification is evaluated and discussed. Cont/d.